Beam Depth Size Effect In Simply Supported Reinforced Concrete Deep Beam - Kok, Eugene Zhen Yin (2022)
Reinforced concrete (RC) deep beam is different from slender beam in term of its load transferring mechanism. It is widely used in construction industry to transfer massive amount of load over a large span length mainly to free up more column spaces. Depth of deep beam would often be increased to withstand higher loading. However, the increase in depth of the beam may not resultes in a corresponding increment in beam shear strength where this phenomenon is referred as depth size effect. Therefore, this research study aims to focus on the depth size effect in simply supported RC deep beam. This research study utilized the ABAQUS Finite Element Analysis (FEA) software to simulate the numerical test specimen. Six numerical deep beam specimens were created which includes one reference beam, R-01, one control beam, C01, and 4 numerical test specimens with different cross-sectional height denoted as D-400, D-500, D-600 and D-700 which were analysed by ABAQUS software. The numerical reference beam results were verified with the experimental results from Zhang and Tan (2007) to prove the reliability of numerical modelling technique. Then, similar numerical modelling technique was applied for all the numerical specimens. The difference in ultimate failure loads between numerical model and analytical model (Cracking Strut and Tie model) are found to range between 5.13% and 7.24%. Besides, size effect was observed in the study. On the first 100 mm beam height increment, the normalized shear stress decreased by 4.29 % and for the following 100 mm beam height incremental, the cumulative decrements are found to be 11.07 %, 13.97 % and 16.95 % respectively. The decrement in relative depth of compression zone is the contributing factor that resulted in size effect. Other than that, the von Mises stress contour and concrete tension damage contour was generated to study the behaviour of deep beam with different height in term of stress distribution and cracking propagation. The findings shows that the stress distribution and crack propagation of numerical deep beam specimens are about similar between each of the specimen. Therefore, it is inferred that the stress distribution and cracking propagation of deep beam does not greatly influence by the specimen’s height.